Proust-Envy: Fiction and Autobiography in the Works of Iurii Olesha - Elizabeth Klosty Beaujour (Studies in 20th & 21st Century Literature, 1977)
Iurii Olesha's works present us with a series of episodes for a fictional autobiography: the self-portrait of the artist as failure. Already early in his career, Olesha was committed to the achievement of success through the creation and manipulation of images of failure. These images are also dominant in his last work No Day Without a Line, which this article analyzes. Olesha declares in No Day that he wishes to "go backwards through life the way Marcel Proust succeeded in doing in his time." There are interesting similarities between the two writers, particularly the fact that A la Recherche du temps perdu is also in a sense based in the imagination of failure. But Olesha misunderstands Proust's procedure, and in so doing reveals much about the nature of his own talent and his inability to come to terms with time.
Keywords: Iurii Olesha; Yury Olesha Marcel Proust; imitation; intertext